2023
DOI: 10.22365/jpsych.2023.006
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary psychiatric hospitalizations in Greece: Contemporary research and policy implications

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published during the production process, errors, may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Conversely, people with mental health problems living in remote areas, such as Orestiada (see Figure 1), face more challenges with regard to the above. Consistent with this finding, a study that was carried out in Thessaloniki, Greece, showed that involuntary admission rates were higher for patients living in regions away from the city [12]. A study carried out in the Canton of Vaud, Switzerland, also found that there is a variation between districts in terms of involuntary admission rates due to disparities in the availability of psychiatric services [19].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Conversely, people with mental health problems living in remote areas, such as Orestiada (see Figure 1), face more challenges with regard to the above. Consistent with this finding, a study that was carried out in Thessaloniki, Greece, showed that involuntary admission rates were higher for patients living in regions away from the city [12]. A study carried out in the Canton of Vaud, Switzerland, also found that there is a variation between districts in terms of involuntary admission rates due to disparities in the availability of psychiatric services [19].…”
Section: Discussionmentioning
confidence: 70%
“…It is worth noting that a little more than half (51%) of the involuntary assessments resulted in involuntary admissions to the psychiatric department of UGHA. In the same period, rates of involuntary assessments turning into involuntary admissions were 96.9% in Athens and 88.5% in Thessaloniki, the two major urban Greek centers [12]. Metropolitan areas probably face more challenges in terms of continuity of care, sectorized organization of mental health services, and integrated care provided by community services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was in Greece, where reform around the locations of mental health centers is still incomplete. According to the Greek expert, decreasing the concentration of psychiatric patients and involuntary psychiatric treatments in some hospitals in large cities such as Athens and Thessaloniki would allow better patient management and less crowding of urban psychiatric hospitals ( 45 ). A second and long-standing problem that respondents highlighted is the underfunding and scarcity of human resources within the mental health area.…”
Section: Resultsmentioning
confidence: 99%